Muscular and glenohumeral changes in the shoulder after brachial plexus birth palsy: an MRI study in a rat model - Soldado, Francisco; Benito-Castillo, David; Fontecha, Cesar G; Barber, Ignasi; Marotta, Mario; Haddad, Sleiman; Menendez, Mariano E; Mascarenhas, Vasco V; Kozin, Scott H (Journal of Brachial Plexus and Peripheral Nerve Injury, 2012)
Background Shoulder abnormalities are the major cause of morbidity in upper brachial plexus birth palsy (BPBP). We developed a rat model of upper trunk BPBP and compared our findings to previously reported animal models and to clinical findings in humans.Methods Forty-three 5-day-old newborn rats underwent selective upper trunk neurectomy of the right brachial plexus and were studied 3 to 20 weeks after surgery. The passive shoulder external rotation was measured and the shoulder joint was assessed bilaterally by a 7.2T MRI bilaterally.Results We found a marked decrease in passive shoulder external rotation, associated with a severe subscapularis muscle atrophy and contracture. None however developed the typical pattern of glenohumeral dysplasia.Conclusions In contradiction with previous reports, our study shows that the rat model is not adequate for preclinical studies of shoulder dysplasia. However, it might serve as a useful model for studies analyzing shoulder contracture occurring after upper BPBP.
Keywords: Shoulder anomalies following brachial plexus birth palsy; Shoulder internal rotation contracture; Glenohumeral dysplasia; Erb’s palsy